2018
DOI: 10.2478/mjss-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles and the Hybrid Learning: An Empirical Study about the Impact of Learning Styles on the Perception of the Hybrid Learning

Abstract: Learning style is a crucial element in the academic life of students. It plays a fundamental role in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…For example, our results showed that the face tendency features typically decreases in online environments due to the sense of distance and anonymity of students. Such a finding is in line with previous studies which noted that online and F2F learning environments are differently effective for students with certain learning styles [84,85]. We recommend practitioners to become sensitive to individual students' learning styles and to allow them more flexibility to organize their own learning.…”
Section: Limitations and Implications For Future Research And Practicesupporting
confidence: 90%
“…For example, our results showed that the face tendency features typically decreases in online environments due to the sense of distance and anonymity of students. Such a finding is in line with previous studies which noted that online and F2F learning environments are differently effective for students with certain learning styles [84,85]. We recommend practitioners to become sensitive to individual students' learning styles and to allow them more flexibility to organize their own learning.…”
Section: Limitations and Implications For Future Research And Practicesupporting
confidence: 90%
“…Pembelajaran kombinasi (blended learning) memiliki sejumlah keuntungan bagi siswa dan guru. Dimana pembelajaran ini memiliki dampak positif pada prestasi akademik siswa, kepuasan siswa, penggunaan sumber daya yang efisien, meningkatkan kemampuan komunikasi siswa (Ora et al, 2018). Selain itu, blended learning sangat mendukung pendidikan di era 4.0 (Hartono et al, 2018).…”
Section: Pendahuluanunclassified
“…Hybrid teaching: is the teaching done face-to-face and online, that satisfies students' needs and education goals (Ora, Sahatcija, & Ferhataj, 2018).…”
Section: Research Conceptsmentioning
confidence: 99%
“…Despite the negative impact of traditional strategies on student achievement, teachers did not extend additional effort on finding more efficient strategies to help their students improve in their accomplishments (Mahmood, 2021;Onyema et al, 2020;Telyani et al, 2021). Despite the negative impact of the strategies used, local educational organizations did not execute any field research to study the impact of the strategies on students' achievement and the teachers' capabilities to design new ones to meet the online or hybrid teaching process (Ora et al, 2018;Sindiani et al, 2020).…”
Section: Teaching Stylesmentioning
confidence: 99%